Indonesian economic recession phenomenon post Covid-19 pandemic - Lativa Lativa (Journal of Economics and Business Letters, 2022)
The covid-19 pandemic caused the emergence of the economic recession phenomenon in Indonesia. This literature review article is used to find out various kinds of phenomena that appear marked by indicators of economic recession and the role of the government in issuing regulations or policies that have been in force in Indonesia in dealing with cases of COVID-19 and to see the impact of the economic recession phenomenon that occurred in Indonesia. Furthermore, prevent economic depression. The economic recession was marked by the weakening of the global economy, the decline in the marginal efficiency of capital, the high unemployment rate, the decline in exports and investment, as well as the decline in state revenues from taxes, and the lowering of the government's economic growth target. The government can prevent a recession from turning into a depression by issuing various policies to provide administrative convenience (permits) and taxes for capital owners (investors) to invest and build various projects by issuing massive budgets